Strategic success according to the strategic alignment A case study of the municipalities of the capital of Baghdad - dawood, Prof.Dr.fadheelahsalman; Mahmoud, Ali Salah Abood (The journal of contemporary issues in business and government, 2021)
The topic of strategic alignment is one of the important topics in the strategic thinking of business organizations through which organizations can have the ability to achieve their strategic goals. In our research, we touched upon the independent variable of strategic alignment in its three dimensions (added value, infrastructure, skills), and strategic success in its dimensions. The three (growth, high implementation, customer satisfaction), as this research was applied to a sample of senior and middle leaders in the Municipality of Baghdad. The strategic alignment is one of the actual steps that organizations take in their natural course to eliminate weakness in internal and external dealings, work environment, And work to address its weaknesses and face all the contradictions and problems that may exist in the work environment, the ability to promote and protect sustainable development and the ability to invest resources within the organization, as a case study methodology was used in the Baghdad Municipality, using checklists, and a set of questions and a scale were used in the research. Seven statistical means (arithmetic mean, frequencies, and extracting the size of the gap) and among the most prominent results The Municipality of Baghdad is not interested in its cadres who have experience and skills, as they affect the relationship between strategic alignment and strategic success.